Poly(benzoxazine) as an Immobilization Matrix for Miniaturized ATP and Glucose Biosensors. Issue 4 (24th March 2017) - Ziller, Charlotte; Lin, Jing; Knittel, Peter; Friedrich, Laura; Andronescu, Corina; Pöller, Sascha; Schuhmann, Wolfgang; Kranz, Christine
Abstract: The reproducible immobilization of enzymes represents a key requirement in developing sensitive and fast‐responding amperometric microbiosensors. A microbiosensor for the respective detection of glucose and adenosine‐5′‐triphosphate (ATP) is presented by using a poly(benzoxazine) derivative for the entrapment of the enzymes glucose oxidase (GOD) and hexokinase (HEX) at platinum (Pt) microelectrodes (MEs). For glucose, a sensitivity of 123.05±10.78 pA/mM ( n =5) was obtained, which shows twice as high sensitivity compared to microbiosensors that use electrophoretic paints as the immobilization matrix for the same size ME (radius: 25 μm). For the determination of ATP, a sensitivity of 48.47±5.12 pA/μM and a signal‐to‐noise ratio of 40 at physiological pH values were obtained. Apart from their enhanced sensitivity, a significant improvement of these sensors is related to their improved mechanical stability. The applicability of these poly(benzoxine)‐based microbiosensors for ATP detection was demonstrated with measurements at receptor protein tyrosine phosphatase zeta (PTPRζ) osteoblastic cells during mechanical stimulation. Abstract : Stressed out : An improved ATP microbiosensor based on poly(benzoxazine) derivative for enzyme entrapment is presented. Such microbiosensors are highly suitable for ATP measurements in the vicinity of live cells exposed to mechanical stress.